Comparative study on communicative competence in bilingual children of the high Andean area of ??the district of Huanta - Quispe Morales, Rolando Alfredo (2020)
The research was carried out with the objective of knowing the difference that exists in the communicative competence in Quechua and Spanish languages ??in students of bilingual educational institutions in the high Andean area of ??the Huanta district. It was reflected in a type of descriptive research and comparative design, in which the observation sheet was used as an instrument for the collection of information. Likewise, the research was carried out in a sample of 40 students of the sixth grade of primary education. The statistician used to test the hypothesis was Mann Whitney's U because the data obtained do not present a normal distribution and are on an ordinal scale. The results obtained allow us to conclude that there are significant differences in communicative competence in the Quechua and Spanish languages ??in students of bilingual educational institutions in the high Andean area of ??the Huanta district.